TRANSLATION PROCEDURE USED IN QUICK REFERENCE OF COMPAQ NOTEBOOK PC - Indah Sari Ayu Nasution; Rahmad Husein; Zainuddin Zainuddin (Universitas Negeri Medan, 2018)
The aims of this study were to find out the types of translation procedures in the translation of Quick Reference of Compaq Notebook PC from English into Indonesian, and to describe the ways of proceduer translated in contextual situation from English into Indonesian. The research was conducted by using descriptive qualitative design. The data of this study were word,phrase,clouse and sentence that were translated from English into Indonesian on a book of “Quick Reference of Compaq Notebook PC as the source of data. Besides that, the data was analyzed by using translation procedure based on (Newmark,1988) which used to answer the questions number one and two to find the types and ways of translation procedure were used in Quick Reference of Compaq Notebook PC.The results of this study were found that there were eleven types of translation procedure used in translation of Quick Reference of Compaq Notebook PC namely transference, naturalization, culture equivalent, functional equivalent, synonymy, through translation, shift or transposition, modulation, recognised equivalent,componential analysis and reduction and expansion.The context of Translation procedure used in Quick Reference of Compaq Notebook PC were context situation based Halliday (1987) which used to answer the question number three.It consists of field,tenor and mode. Keywords: Quick Reference, Compaq Notebook PC, Translation Strategies